Strategi Menyampaikan Keinginan Kalam Bahasa Jepang: Kajian Hairyo Hyougen - Radhia Elita (Masyarakat Linguistik Indonesia Universitas Andalas, 2013)
In interaction, there must be some variations occur due to the variation of social status or age. This might be brought about by situation and condition in communication process. For example is when delivering the desires to ask for time or to ask for dating. Offering tea is one strategy to exprees the desire in Japanesse culture. Indirect speech act commonly well-known as indirect culture (kansetsusei) is a kind of distinctive way of Japanesee people. This indirect speech act is also calledÂ kansetsuteki hatsuwa koui. The indirect speach act in airyo hyougenÂ is aÂ strategy used to save interlocutor's face.